High-melting-point high-entropy alloy coating for laser cutting rack and preparation method and application of high-melting-point high-entropy alloy coating
By using a high melting point high-entropy alloy MoFeCrTiW(TiC)X coating on the laser cutting rack, the laser cladding technology is used to solve the problem of damage to the rack during laser cutting, achieving high-temperature ablation isolation of the rack and reducing the crack depth and width, and extending the service life of the rack.
Patent Information
- Application Number
- CN202510008204.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-18
AI Technical Summary
During laser cutting, high-power and high-temperature lasers irradiate through the steel plate to the material rack area, resulting in wide and deep obvious cracks in the material rack, which seriously weakens the service life of the material rack. The existing research on high-temperature resistant materials has not kept up with the rapid development of laser cutting technology.
The high melting point high entropy alloy MoFeCrTiW(TiC)X is used as the coating material, and the coating is applied to the surface of the material rack by laser cladding technology. In the alloy molecular formula, x means that the mass of TiC is 0%-20% of the total mass of MoFeCrTiW. The ball milled alloy powder is pre-placed on the surface of the substrate and the coating is prepared using a broadband laser cladding equipment.
It effectively isolates high-temperature ablation, reduces the depth and width of cracks generated by the rack base material during laser cutting, extends the service life of the rack, and improves cutting accuracy and efficiency.
Smart Images

Figure CN119843269A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of alloy technology, specifically to a high-melting-point, high-entropy alloy coating for laser cutting feeders, its preparation method, and its application. Background Technology
[0002] Laser cutting is one of the earliest, most widely used, and most important technologies in laser processing, and it is also the most advanced cutting process in the world today. It boasts advantages such as a wide cutting range, high precision, high cutting speed, narrow kerf, one-time forming, small heat-affected zone, high processing flexibility, and high efficiency. It is widely used in modern industry, accounting for over 70% of the entire laser processing industry, and can solve many problems in industrial production that traditional methods cannot address. However, despite the rapid development of the laser cutting industry, there is currently a general lack of attention to the protection of laser cutting support frames. Research on high-temperature resistant materials used in laser cutting equipment has not kept pace with the rapid development of laser cutting technology. During the laser cutting process, the high-power, high-temperature laser light penetrating the steel plate and irradiating the support frame area causes wide and deep cracks, severely damaging the support frame and drastically reducing its lifespan. Prolonged exposure to this condition reduces the precision and efficiency of laser cutting steel plates. Currently, the only solution for laser cutting support frames is frequent replacement. However, this inevitably places a heavy burden on production costs, causing significant losses for enterprises. Therefore, providing a material that can adhere to the surface of the material rack and has excellent high-temperature resistance and ablation resistance, as well as a preparation method, is of great significance to the laser cutting industry.
[0003] High-entropy alloys were first proposed by Professor Ye Junwei in 2004. By controlling the composition of alloying elements, high-entropy alloys can possess high-temperature resistance, ablation resistance, and wear resistance, making them promising materials. High-entropy alloys, also known as multi-component alloys, have ≥5 principal elements, with each element alloyed in an equiatomic or near-equiatomic ratio, and each element's content ranging from 5% to 35%. This new concept of high-entropy alloys provides a new approach to developing new materials. High-entropy alloys exhibit superior properties compared to traditional Fe, Ti, and Ni-based alloys, such as a simple solid solution structure and excellent high-temperature stability. They also demonstrate high hardness and strength, excellent corrosion resistance, and wear resistance, making them promising for applications in high-speed cutting tools, various molds, turbine blades, and other fields.
[0004] Laser cladding is a surface modification technology that involves irradiating a coating material onto a substrate surface with a laser, causing both the coating material and a thin layer on the substrate surface to melt simultaneously. This rapidly solidifies to form a coating with extremely low dilution and a metallurgical bond to the substrate, thereby improving the substrate's wear resistance and corrosion resistance. Firstly, the rapid heating and high cooling rates of laser cladding result in a higher grain nucleation rate than growth rate, leading to refined and supersaturated solidification structures. This allows for the in-situ precipitation of uniform solid solutions and micro / nano-sized dispersed phases, resulting in fine grains that enhance the strength, hardness, and corrosion resistance of the alloy material. Secondly, laser cladding produces coatings with uniform microstructures, controllable thicknesses down to the millimeter level, and significant savings in precious metals, facilitating automated production. Therefore, laser cladding is chosen as a process for preparing high-entropy alloys to obtain alloy materials that are resistant to high temperatures, ablation, and wear. Summary of the Invention
[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a high melting point high entropy alloy coating for laser cutting material holders, its preparation method and application, which can effectively isolate high temperature ablation, reduce the depth and width of cracks in the material holder substrate during laser cutting, and protect the substrate.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: a high-melting-point, high-entropy alloy coating for laser cutting material holders, characterized in that: the alloy molecular formula is: MoFeCrTiW(TiC). X According to the mass ratio, x represents the mass of TiC being 0%-20% of the total mass of MoFeCrTiW.
[0007] In the above scheme, x is 5-15%.
[0008] A method for preparing a high-melting-point, high-entropy alloy coating for laser cutting feeders, characterized by the following steps:
[0009] 1) Accurately weigh the Mo, Fe, Cr, Ti, and W powders;
[0010] 2) Add TiC powder;
[0011] 3) Place the weighed powder into a ball mill jar and ball mill it to mix the alloy powder evenly. Then dry, sieve, and store it in a dry place.
[0012] 4) Select 45# steel as the base material, clean and remove surface oil, and use a sander to grind the surface of the base material to remove the surface oxide scale until a bright surface is exposed.
[0013] 5) Using the pre-powder method, the ball-milled alloy powder is pre-placed on the polished surface of the substrate to pre-coat the alloy powder thickness, and the coating is prepared using broadband laser cladding equipment.
[0014] In the above scheme, in step (3), the ball-to-material ratio is 5:1, the ball milling speed is 350-500 rpm / min, and the ball milling time is 1.5-2h.
[0015] In the above scheme, the particle size of Mo, Fe, Cr, Ti, W, and TiC powders is 45-105 μm, and the purity is ≥99.9%.
[0016] In the above solution, alcohol is used to clean and remove oil stains from the substrate surface.
[0017] In the above scheme, step 5) uses an RC-LMS-6000-R fiber laser with the following laser cladding parameters: laser power P = 5000W, scanning rate v = 7mm / s, and rectangular spot size 20×2mm. 2 The airflow density is 15 L / min.
[0018] The application of the high-melting-point, high-entropy alloy coating described above as a coating on a laser cutting material holder.
[0019] The MoFeCrTiW high-melting-point high-entropy alloy used in this invention is a novel alloy composed of multiple refractory elements, possessing excellent comprehensive properties such as high-temperature mechanical properties, high-temperature oxidation resistance, tribological wear resistance, corrosion resistance, and radiation resistance. However, the MoFeCrTiW high-melting-point high-entropy alloy has poor hardness. Introducing hard TiC particles into the high-entropy alloy composition improves its hardness. Simultaneously, the pinning effect of the hard TiC particles restricts grain growth, effectively refining the grains and promoting coating hardness through grain refinement strengthening. TiC in the hard particles possesses high hardness, high modulus, and excellent high-temperature oxidation and corrosion resistance. This invention, by adding TiC to comprehensively regulate the properties of the high-entropy alloy composition, yields a high-temperature resistant, ablation-resistant coating with certain wear resistance when clad onto 45# steel.
[0020] The prepared high-entropy alloy coating has the characteristics of high temperature resistance and ablation resistance. Under the irradiation of high-energy laser beam, the high-entropy alloy coating fused on the substrate surface effectively isolates high-temperature ablation and reduces the depth and width of cracks in the substrate during laser cutting, thus protecting the substrate. Attached Figure Description
[0021] Figure 1 For MoFeCrTiW(TiC) X (x = 0, 0.05, 0.1, 0.15, 0.2) XRD pattern of laser cladding coating.
[0022] Figure 2 For MoFeCrTiW(TiC)X Microhardness diagram of laser cladding coating.
[0023] Figure 3 For MoFeCrTiW(TiC) X Average hardness of laser cladding coating.
[0024] Figure 4 For MoFeCrTiW(TiC) X Topographic image of the coating.
[0025] Figure 5 For MoFeCrTiW(TiC) X The microstructure of the middle part of the coating.
[0026] Figure 6 For MoFeCrTiW(TiC) X Image of the coating interface morphology.
[0027] Figure 7 For MoFeCrTiW(TiC) 5% EDS surface scan of the coating.
[0028] Figure 8 For MoFeCrTiW(TiC) 5% Comparison of macroscopic morphology of coated samples and substrate samples during laser cutting field tests at the factory.
[0029] Figure 9 For MoFeCrTiW(TiC) 0.05 ,MoFeCrTiW(TiC) 0.1 Comparison of macroscopic morphology between coated samples and substrate samples after laser cutting field test. Detailed Implementation
[0030] The present invention will be further described in detail below through specific embodiments:
[0031] Example 1
[0032] 1) Composition design: Using MoFeCrTiW high-entropy alloy as the matrix, 0%, 5%, 10%, 15%, and 20% by mass of TiC powder were added to the matrix to obtain MoFeCrTiW(TiC). X High-entropy alloy cladding coating. Chemical composition is shown in Table 1;
[0033] Table 1 shows the chemical composition of the MoFeCrTiW high-entropy alloy.
[0034]
[0035] Among them, MoFeCrTiW(TiC) XIn this context, x represents the mass ratio of the total mass of Mo, Fe, Cr, Ti, and W.
[0036] The Mo, Fe, Cr, Ti, W, and TiC powders selected have a size of 45-105 μm and a purity of ≥99.9%.
[0037] The powder was prepared according to Table 1 and weighed using an AL204 electronic balance with an accuracy of 0.001g.
[0038] 2) Powder ball milling: Place the prepared powder in a stainless steel ball mill jar for ball milling. Milling parameters: ball-to-powder ratio 5:1, milling speed 350-500 rpm / min, milling time 1.5-2 hours. After milling, sieve the powder through an 80-mesh stainless steel sieve, then dry and store the sample.
[0039] 3) Substrate selection: 45# steel with dimensions of 50mm × 30mm × 10mm was selected as the substrate. The substrate surface was cleaned with alcohol to remove oil stains, and the oxide scale was removed using a grinding wheel. The surface oil was then cleaned with alcohol and dried with a hair dryer before use.
[0040] Laser cladding coating preparation: A pre-powder method was used, in which a 1.5mm thick layer of powder was pre-placed on the substrate surface using a mold. A high-melting-point, high-entropy alloy coating was prepared using a broadband cladding laser. The laser used was an RC-LMS-6000-R fiber laser, and argon gas was used for protection during the cladding process. The laser cladding parameters were: laser power P = 5000W, scanning rate v = 7mm / s, and rectangular spot size 20×2mm. 2 The airflow density is 15 L / min.
[0041] Figure 1 For MoFeCrTiW(TiC) X As can be seen from the XRD image above, the coating is mainly composed of BCC solid solution, C14-Laves phase, and MC-type carbides.
[0042] Table 2 MoFeCrTiW(TiC) X Coating microhardness table
[0043]
[0044] Figure 2 For MoFeCrTiW(TiC) X Microhardness diagram of laser cladding coating. Appropriate laser power can decompose TiC and integrate it into the matrix; however, a large amount of TiC results in some unmelted material, thus forming MoFeCrTiW(TiC). 0.05The average hardness is lowest at TiC. As the TiC content exceeds 5%, the average hardness of the coating also increases. Therefore, TiC particles can improve the hardness of the coating within a certain range. This is because a large number of unmelted second-phase particles exist in the matrix, thereby producing dispersion strengthening and increasing hardness.
[0045] Figure 3 For MoFeCrTiW(TiC) X The average hardness of the laser cladding coating shows that as the TiC content increases, the average hardness first decreases, then increases, and then decreases again. The coating has the lowest average hardness (730.2 HV) when x = 0.05. 0.2 As TiC increases further, the average hardness also gradually increases. When x = 0.15, the average hardness reaches its maximum, three times that of the matrix, mainly due to solid solution strengthening and dispersion strengthening. However, when TiC exceeds a certain value, the hardness decreases again.
[0046] Figure 4 For MoFeCrTiW(TiC) X The microstructure of the upper layer of the coating is shown in the images, where (a) 0 wt% TiC, (b) 5 wt% TiC, (c) 10 wt% TiC, (d) 15 wt% TiC, and (e) 10 wt% TiC, from MoFeCrTiW(TiC). X Analysis of the microstructure of the upper layer of the coating revealed that the grain morphology mainly consisted of dendrites and cellular crystals. Without TiC, the coating exhibited numerous porosity defects. As the TiC content gradually increased, the grain size in the coating gradually decreased. However, when the TiC content reached 20%, the coating grains coarsened, accompanied by the appearance of second-phase particles. Excessive TiC particles increased the thermal and mechanical stress between the coating and the substrate, leading to significant cracks and porosity. This accelerated the detachment of hard TiC particles from the coating surface, thereby reducing the mechanical properties of the coating.
[0047] Figure 5 For MoFeCrTiW(TiC) X The microstructure of the coating is shown in the images, where (a) 0 wt% TiC, (b) 5 wt% TiC, (c) 10 wt% TiC, (d) 15 wt% TiC, and (e) 10 wt% TiC, from MoFeCrTiW(TiC). XAnalysis of the microstructure in the middle of the coating reveals that the number of pores in the middle is relatively less than that in the upper part. The pinning effect of hard particles restricts grain growth, and due to the high melting point of TiC, the nucleation rate of crystals is increased during laser cladding, thus promoting grain refinement. As shown in the figure, when the TiC content is between 5% and 15%, the grain size is significantly smaller than at other contents. This is because the large temperature difference at the solid-liquid interface allows grains to grow continuously along the matrix direction, while the cooling rate in the middle of the molten pool is slower, giving the grains sufficient time to grow along the heat flow direction, thus forming dendrites.
[0048] Figure 6 For MoFeCrTiW(TiC) X Microstructure of the coating interface, from MoFeCrTiW(TiC) X Analysis of the microstructure of the coating interface reveals that when the TiC content is between 5% and 15%, the dendritic grains in the coating become elongated, nucleating and growing into columnar dendrites at the bottom of the molten pool. Subsequently, due to the irregular diffusion of heat within the molten pool, new nucleation sites appear on the columnar dendrites, gradually growing to form ovoid dendrites. The figure shows a distinct bright white band at the bottom of the molten pool, indicating that the coating and substrate are connected through metallurgical bonding. Metallurgical bonding refers to the bonding formed by the interdiffusion of atoms at the interface of two metals. This bonding allows the metal to undergo various cold and hot pressure forming, welding, and machining processes, which is incomparable to the interface of cold composite materials bonded only by mechanical bonding or van der Waals forces.
[0049] Table 3 MoFeCrTiW(TiC) 0.05 Coating EDS Spot Scan Data Sheet
[0050]
[0051]
[0052] Figure 7 For MoFeCrTiW(TiC) 5% EDS surface scan of the coating, obtained by analyzing the MoFeCrTiW(TiC) coating. 0.05 EDS surface and spot scan data analysis of the coating revealed that Mo was enriched at the grain boundaries, while W was enriched in the dendritic regions. Furthermore, C content was higher than Ti content at both the dendrites and grain boundaries, and both C and Ti content were higher at the grain boundaries than in the dendritic regions. This is because after the TiC particles dissolved, the precipitated Ti and C elements were enriched at the grain boundaries and subsequently nucleated and grew, forming carbide precipitates. The fine, unmelted TiC particles were uniformly distributed on the substrate surface, which increased the hardness of this high-melting-point, high-entropy alloy coating to more than three times that of the substrate.
[0053] Figure 8 For MoFeCrTiW(TiC) 5% Comparison of macroscopic morphology between layer sample and substrate sample during laser cutting field test at the factory.
[0054] High-melting-point, high-entropy alloy samples were laser-clad using two laser processes: a 20mm thick steel plate with a laser power of 24000W and a cutting speed of 3000mm / min, and an 8mm thick steel plate with a laser power of 15000W and a cutting speed of 8000mm / min. The cutting depths were measured, with the substrate samples showing a laser cutting depth of 0.85–1.00mm and the coating samples showing a laser cutting depth of 0.45mm–0.55mm. Clearly, laser cladding of MoFeCrTiW(TiC)... 0.05 The high-melting-point, high-entropy alloy coating reduces the depth of damage to the material rack by about half, effectively mitigating damage to the material rack during laser cutting.
[0055] Figure 9 For MoFeCrTiW(TiC) 0.05 ,MoFeCrTiW(TiC) 0.1 A comparison of the macroscopic morphology of the coated samples and the substrate samples after laser cutting in a field test. To further verify the effectiveness of the experimental process, a 12mm thick steel plate was used to cut the substrate sample, the 5% TiC coated sample, and the 10% TiC coated sample using a laser with a power of 8000W and a cutting speed of 2000mm / min. The cutting depth was measured. The laser-cut crack depth of the substrate sample was 0.15mm–0.3mm, and the crack width was 0.26mm–0.3mm, with obvious slag appearing on the surface. In contrast, the 5% TiC coated sample had almost no residue and no cracks, while the 10% TiC coated sample had slag on the surface and slight cracks with a depth of 0–0.1mm and a width of 0–0.15mm. These results indicate that the 5% TiC coated sample has a superior improvement effect, effectively reducing damage to the material rack and significantly extending its lifespan.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not limiting. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A high melting point high entropy alloy coating for laser cutting racks, characterized in that: The alloy formula is: MoFeCrTiW(TiC) X , according to the mass ratio, x represents that the mass of TiC is 0%-20% of the total mass of MoFeCrTiW.
2. The high-entropy alloy coating with high hardness and high wear resistance according to claim 1, characterized in that: The x is 5-15%.
3. A method for preparing a high melting point high entropy alloy coating for laser cutting of a material rack according to any one of claims 1 to 2, characterized in that: Prepare according to the following steps: 1) Accurately weigh Mo, Fe, Cr, Ti, and W powders; 2) Adding TiC powder; 3) Put the weighed powder into a ball mill, ball mill it to make the alloy powder evenly mixed, then dry it, sieve it, and store it in a dry place; 4) Select 45# steel as the substrate, clean and remove the surface oil, and use a sand grinder to grind the surface of the substrate to remove the surface oxide scale until the bright surface is exposed; 5) Using the pre-powder method, the ball-milled alloy powder is pre-placed on the polished surface of the substrate, the alloy powder thickness is pre-coated, and the coating is prepared using broadband laser cladding equipment.
4. The method for preparing a high melting point high entropy alloy coating for laser cutting of a material rack according to claim 3, characterized in that: In step (3), the ball-to-material ratio is 5:1, the ball milling speed is 350-500 rpm / min, and the ball milling time is 1.5-2 h.
5. The method for preparing a high melting point high entropy alloy coating for laser cutting of a material rack according to claim 4, characterized in that: The particle sizes of Mo, Fe, Cr, Ti, W and TiC powders are all 45-105 μm, and the purity is ≥99.9%.
6. The method for preparing a high melting point high entropy alloy coating for laser cutting of a material rack according to claim 5, characterized in that: Use alcohol cleaning to remove oil stains on the surface of the substrate.
7. The method for preparing a high melting point high entropy alloy coating for laser cutting of a material rack according to claim 6, characterized in that: In step 5), the laser model used is RC-LMS-6000-R fiber laser, and the laser cladding parameters are: laser power P = 5000W, scanning rate v = 7mm / s, rectangular spot size 20×2mm 2 , air flow density is 15L / min.
8. Use of the high melting point high entropy alloy coating for laser cutting racks according to any one of claims 1 to 2 as a coating on a laser cutting rack.